2023
DOI: 10.3390/ijms24010847
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Electrical Signals and Phytohormones in the Control of Systemic Response

Abstract: Plants are constantly exposed to environmental stresses. Local stimuli sensed by one part of a plant are translated into long-distance signals that can influence the activities in distant tissues. Changes in levels of phytohormones in distant parts of the plant occur in response to various local stimuli. The regulation of hormone levels can be mediated by long-distance electrical signals, which are also induced by local stimulation. We consider the crosstalk between electrical signals and phytohormones and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 177 publications
1
6
0
Order By: Relevance
“…The results suggested transmission of a mobile wound signal from damaged leaves to distal ones, and it seemed logical to attribute this role to jasmonates. However, a more complex mechanism has been discovered involving an electrical signal, which mediates stimulation of JA production in distal leaves themselves [ 61 , 62 ]. Nevertheless, the translocation of jasmonates from local to distal leaves has been found in Arabidopsis, a process regulated by jasmonate transporters expressed in the phloem and localized in the plasmalema [ 63 ].…”
Section: Long-distance Transport Of Jasmonic Acid Jasmonates and Rela...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested transmission of a mobile wound signal from damaged leaves to distal ones, and it seemed logical to attribute this role to jasmonates. However, a more complex mechanism has been discovered involving an electrical signal, which mediates stimulation of JA production in distal leaves themselves [ 61 , 62 ]. Nevertheless, the translocation of jasmonates from local to distal leaves has been found in Arabidopsis, a process regulated by jasmonate transporters expressed in the phloem and localized in the plasmalema [ 63 ].…”
Section: Long-distance Transport Of Jasmonic Acid Jasmonates and Rela...mentioning
confidence: 99%
“…Jasmonates have been shown to be involved not only in responses to biotic but also abiotic stresses [ 12 ]. Wounding as well as light and heat stress and other local stimuli can induce electrical signals to propagate over long distances, mediating hormone levels in distant organs [ 62 ]. It was shown that electrical signals are accompanied by changes in pH, Ca 2+ , and ROS levels, which induce changes in the activity of downstream responders regulating JA biosynthesis.…”
Section: Long-distance Transport Of Jasmonic Acid Jasmonates and Rela...mentioning
confidence: 99%
“…This collection also contains reports on the action of plant growth regulators recently classified as phytohormones: strigalactones [5] and melatonin [3,7]. Hormonal control of plant growth and development is discussed in connection with the development of plant resistance to stress conditions [5,7,11]. The novelty of the collection presented in this SI lies in demonstrating new aspects of hormonal control of physiological processes: the disturbance of hormonal balance in a maize mutant characterized by unusually large embryo [2], the involvement of ABA in the control of the movement of water lily flower petals [1], melatonin-induced increase in cherimoya fruit resistance to chilling [3], hormonal control of accumulation of storage proteins in Yellow lupin [4], identification of genes responsible for the synthesis of strigolactones in Chimonanthus praecox and their involvement in shoot branching [5], discovery of cytokinin ability to slow down the formation of Casparian bands in transgenic tobacco plants [6] and interaction of cytokinins with melatonin in the control of plant resistance to high light stress [7], identification of the YUCCA genes in Mikania micrantha [8], regulation of PIN-formed (PIN) auxin transporters by their degradation [9], interaction of hormonal and electrical signals in plants [11].…”
mentioning
confidence: 99%
“…The final article in this collection addresses a very interesting and rarely discussed topic: the interaction of hormonal and electrical signals in plants and their importance in controlling stress responses at the whole plant level [11]. A hydraulic signal is a wave of increased hydraulic pressure, which rapidly propagates through xylem vessels, with the speed of propagation reaching tens of cm/s [70,71].…”
mentioning
confidence: 99%
“…The change electrical signaling as response of the plant to herbivory is a universal and fast reaction to external stimuli. 3 Among the various biotic stress factors, herbivory is one of the most prevalent, affecting plant lives. Herbivory is caused by mammals or phytophagous insects, and in addition to damaging plant tissue, it also opens “doors” for the attack of pathogenic microorganisms that cause disease, which in turn characterizes another stress factor.…”
mentioning
confidence: 99%